Etiopathology of HRID Rogas WSR to CVDS - Review Article: A holistic approach to preventing and managing cardiovascular diseases (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Cardiovascular diseases (CVDs) are the leading cause of death globally, taking anestimated 17.9 million lives each year. CVDs are a group of disorders of the heart and blood vessels andinclude coronary heart disease, cerebrovascular disease, rheumatic heart disease and other conditions.CVDs are no longer limited to people with age more than 45 years. With advancing time it is affectingyoungsters as well, due to obvious reasons. Heart is the most important organ that supports the life ofan individual. Acharya Charaka and Sushruta both stated Hridaya as Moolasthana of Pranavaha andRasavaha Srotas which leads to inclusion of Hriday in Dashpraanaytanas.As per Ayurveda thesymptoms of various cardio-vascular diseases resembles to that of Hridrogas. Due to such highincidence Hridroga is considered as a major thing of concern to medical field and a seriousresponsibility of Ayurvedic practitioners to combat with it, by implementation of Siddhant as mentionedin Samhitas.As per Ayurvedic literature Heart diseases are correlated with Hrid Rogas. Hrid Rogas arecaused due to variety of reasons most procuring is disturbed lifestyle and mental stress. The presentliterary research deals with prevention of these disorders by awareness in general public regarding theprobable reasons of Hridrogas which are often severe and fatal. The awareness in general public canlead to prevention of heart related disorders. The first purpose of Ayurveda being prevention of diseasesNidana Parivarjan (Mansik and Sharirik) must be executed. The diet and lifestyle must be followedremembering the heart health. Rasayan Sevan is one of the best ways to pursue heart health.